Aporte al estudio sobre la incidencia de los fenomenos patologicos en puentes de hormigon armado en el Uruguay - Franco, José Claudio Barboza (2012)
The study of pathological manifestations in concrete emerges as a valuable tool for understanding the processes involved, in it as long as it makes possible to optimize its use in all stages of the construction process. Under this circumstance it was considerate valid to make a survey about the major damages in Uruguay, for which 93 reports were labeled with 313 assessments on 147 bridges in the period 2004 / 2010. From their analyst’s it was verified of injury "Corrosion of reinforcement", located mainly in the coastal South. Makeover, it was found that "Board" is the most affected of the elements followed by “Side Shields" and "Sidewalks", where "Exposed reinforcement" and "Humidity stains" are the most prevalent problems.